2018
DOI: 10.1111/sms.13337
|View full text |Cite
|
Sign up to set email alerts
|

Association of sedentary time and physical activity during pregnancy with maternal and neonatal birth outcomes. The GESTAFIT Project

Abstract: Aim: (a) To analyse the association of objectively measured sedentary time (ST) and physical activity (PA) during early second trimester of pregnancy with maternal and neonatal birth outcomes; (b) to explore if ST and PA differ between women with vaginal or caesarean section deliveries. Methods: Ninety-four Caucasian pregnant women (32.9 ± 4.6 years old) participated in this prospective longitudinal study. Triaxial accelerometers were used to assess ST and PA intensity levels for seven consecutive days during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 33 publications
3
27
1
8
Order By: Relevance
“…These figures are consistent with accelerometer data among a sociodemographically diverse sample of women at less than 25 weeks of pregnancy in Norway, which showed step counts ranging from 7718 to 9603 depending on ethnicity [31]. Similar studies among Caucasian women in Spain assessed at 16 weeks' gestation showed an average of 7745 steps per day [32]. Systematic reviews highlight that both the frequency and intensity of physical activities tend to decline over the course of pregnancy [33], consistent with the trend toward decline from Evaluation 1 to Evaluation 3 observed in our study.…”
Section: Physical Activitysupporting
confidence: 86%
“…These figures are consistent with accelerometer data among a sociodemographically diverse sample of women at less than 25 weeks of pregnancy in Norway, which showed step counts ranging from 7718 to 9603 depending on ethnicity [31]. Similar studies among Caucasian women in Spain assessed at 16 weeks' gestation showed an average of 7745 steps per day [32]. Systematic reviews highlight that both the frequency and intensity of physical activities tend to decline over the course of pregnancy [33], consistent with the trend toward decline from Evaluation 1 to Evaluation 3 observed in our study.…”
Section: Physical Activitysupporting
confidence: 86%
“…It is widely known that the umbilical cord blood pH analysis provides vital information about neonatal health status and reflects physiological response to complications that may occur during labour [19]. We previously found that higher levels of light or moderate physical activity during pregnancy were associated with greater umbilical arterial oxygen saturation and higher levels of venous cord blood pH; conversely, we showed that higher levels of sedentary time during pregnancy were related to worse pregnancy outcomes [10]. However, it is unknown whether maternal physical fitness is also a key factor to improve birth outcomes such as gestational age, duration of labour, birth weight and values of umbilical cord blood gas.…”
Section: Introductionmentioning
confidence: 64%
“…Improved physical fitness is usually observed in women who exercise during pregnancy [6] and is associated with better perinatal health outcomes [7,8]. However, while it is well-established that physical activity improves birth outcomes [9][10][11], studies looking at the relationships between objective assessments of fitness and delivery type, gestational age, duration of labour stages, birth weight and values of umbilical cord blood gas are limited. The causes of caesarean sections and how to reduce caesarean section rates are now a spotlight of research as this type of delivery has been associated with an increased risk of infection compared with vaginal deliveries, higher wound dehiscence, haemorrhage and reduced fertility [12][13][14], as well as an increased risk of allergies, type 1 diabetes or respiratory problems [15] in infants, among other complications.…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence also suggests that PA levels are lower in the 3rd trimester than in either the 1st or 2nd trimesters [24,29,30,33,34]. Despite its numerous benefits, studies report that only between a one-fifth [29,31,33,35,36] or one-third [30,37,38] of pregnant women meet PA recommendations. However, the former studies calculated those rates using time bouts.…”
Section: Physical Activity During Pregnancy: On Guidelines Performanmentioning
confidence: 99%